Mannan detecting C-type lectin receptor probes recognise immune epitopes with diverse chemical, spatial and phylogenetic heterogeneity in fungal cell walls - Vendele,I; Willment,JA; Silva,LM; Palma,AS; Chai,W; Liu,Y; Feizi,T; Spyrou,M; Stappers,MHT; Brown,GD; Gow,NAR (PLoS Pathogens, 2020)
During the course of fungal infection, pathogen recognition by the innate immune system is critical to initiate efficient protective immune responses. The primary event that triggers immune responses is the binding of Pattern Recognition Receptors (PRRs), which are expressed at the surface of host immune cells, to Pathogen-Associated Molecular Patterns (PAMPs) located predominantly in the fungal cell wall. Most fungi have mannosylated PAMPs in their cell walls and these are recognized by a range of C-type lectin receptors (CTLs). However, the precise spatial distribution of the ligands that induce immune responses within the cell walls of fungi are not well defined. We used recombinant IgG Fc-CTLs fusions of three murine mannan detecting CTLs, including dectin-2, the mannose receptor (MR) carbohydrate recognition domains (CRDs) 4–7 (CRD4-7), and human DC-SIGN (hDC-SIGN) and of the β-1,3 glucan-binding lectin dectin-1 to map PRR ligands in the fungal cell wall of fungi grown in vitro in rich and minimal media. We show that epitopes of mannan-specific CTL receptors can be clustered or diffuse, superficial or buried in the inner cell wall. We demonstrate that PRR ligands do not correlate well with phylogenetic relationships between fungi, and that Fc-lectin binding discriminated between mannosides expressed on different cell morphologies of the same fungus. We also demonstrate CTL epitope differentiation during different phases of the growth cycle of Candida albicans and that MR and DC-SIGN labelled outer chain N-mannans whilst dectin-2 labelled core N-mannans displayed deeper in the cell wall. These immune receptor maps of fungal walls of in vitro grown cells therefore reveal remarkable spatial, temporal and chemical diversity, indicating that the triggering of immune recognition events originates from multiple physical origins at the fungal cell surface.